The innovation patterns of firms in low and high technology manufacturing sectors in the new member states - Ewa Balcerowicz; Marek Pęczkowski; Anna Wziątek-Kubiak (Center for Social and Economic Research (CASE), 2009)
For many years, analysis on innovations focused on high technology industries which were treated as synonymous with high competitiveness and growth. New research on low and medium technology industries has revealed that their growth is also based on innovations, though their sources differ from high technology industries. As the 'catching up' economies of the EU New Member States (NMS) are based on low and medium technology industries, the differences in innovativeness between high and low technology sector firms as well as within each of the sectors can play an important role in the future development of these countries. This paper aims to show the differences in innovation patterns among manufacturing firms operating in low and high technology sectors in the Czech Republic, Hungary and Poland. It is based on a survey of firms which took into account innovation inputs, cooperation among firms in R&D activities, the benefits of cooperation with business partners, innovation outputs and international competitiveness. The sample consisted of 358 firms operating in both low and medium technology industries (food and beverages and automotive) and high technology industries (pharmaceuticals and electronics). After employing cluster analysis, five types of innovation patterns were detected, characterised and compared in firms operating in the low and medium technology (LMT) sectors, and four in the high technology (HT) sector. Differences and similarities in innovation patterns between firms operating in each of the two sectors are discussed. The paper shows that external knowledge plays a crucial role in innovation activities in NMS' firms. The ability to explore cooperation with business partners and the use of external knowledge are more important for the international competitiveness of the NMS' products than in-house innovation resources.
Keywords: L25; O31; O32; O33; 330; Innovation of firms; Innovation patterns; Innovation sources; Diversification of innovations; Low-tech industries; High-tech industries; EU New Member States; Innovation; Innovationsmanagement; Hochtechnologie; Low-Tech; Industrie; EU-Mitgliedschaft